Rise and fall of Maritime Hubs in Pre-Islamic Arabia - Asmahan Al Garoo (Journal of Arts and Social Sciences, 2018)
Since prehistoric times, the geography of the Arabian Peninsula had a great impact on the growth and development of centers of civilization and maritime hubs. Indeed, starting from the third millennium BC, a number of urban centers of civilization have emerged in the Arab region such as Mesopotamia, Magān (old name of Oman), Dilmun (Bahrain), Pharaonic Egypt, Phoenicia, the Nabataeans, and the ancient South Arabia (Yemen) where such centers reached a high level of development and growth. Arab trade reached a peak in the 1st millennium BC due to the commerce of frankincense and myrrh. The Arabs, who had mastered sea navigation through geographical and astronomical knowledge and had a great experience of maritime routes as well as the secrets of the monsoon and boat industry, dominated the vast eastern trade. During the fourth century AD, the world began to see signs of serious conflicts with religious dimensions and huge political and economic consequences. Furthermore, the lucrative Arab trade of incense lost its importance because of the demise of paganism in the Middle East and Europe. With the emergence of Islam, the Arabs regained their lost maritime domination in the Indian Ocean.